1987
DOI: 10.1111/j.1467-8306.1987.tb00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Clustering and the Organization of Production: A Point Pattern Analysis of Manufacturing in Cincinnati, Ohio

Abstract: The clustering of urban manufacturers occurs for a number of reasons; this paper focuses on the importance of production technology in understanding the degrcc of industrial clustering. The present analysis uses a sample of Cincinnati manufacturing plants to test scveral hypothescs that address the relationships between industrial clustering and industrial production technology. Most of the tests use second-order methods to distinguish between the spatial distributions of specificd classes of industry. The ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 32 publications
1
30
0
1
Order By: Relevance
“…The seminal work by Ripley (1976Ripley ( , 1977 introduced the best known of the existing distance-based methods: the K function. The latter was taken up quickly by field scientists in ecology (see handbooks by Diggle, 1983;Cressie, 1993, for instance) but its use remained incidental in economics (Arbia, 1989;Arbia and Espa, 1996;Barff, 1987;Feser and Sweeney, 2000;Sweeney and Feser, 1998) until the works of Puech (2003, 2010) and Duranton and Overman (2002) 1 who introduced an alternative approach.…”
Section: Introductionmentioning
confidence: 99%
“…The seminal work by Ripley (1976Ripley ( , 1977 introduced the best known of the existing distance-based methods: the K function. The latter was taken up quickly by field scientists in ecology (see handbooks by Diggle, 1983;Cressie, 1993, for instance) but its use remained incidental in economics (Arbia, 1989;Arbia and Espa, 1996;Barff, 1987;Feser and Sweeney, 2000;Sweeney and Feser, 1998) until the works of Puech (2003, 2010) and Duranton and Overman (2002) 1 who introduced an alternative approach.…”
Section: Introductionmentioning
confidence: 99%
“…Por ejemplo, en Cincinnati (Barff, 1987), Los Ángeles (Giuliano y Small, 1991), así como en Toronto, Montreal y Vancouver (Shearmur y Coffey, 2002), hay aglomeraciones fabriles similares a los nodos industriales que se identifican en la urbe mexicana. Como resultado de estudios semejantes a los anteriores, se han creado modelos urbanos que pretenden determinar los patrones espaciales de la distribución industrial.…”
Section: Megacorredor Industrial Históricamente Construidounclassified
“…Point pattern analysis has already been used successfully to analyze industrial location patterns (Barff, 1987;Feser and Sweeney, 2000;Duranton and Overman, 2008). More than two decades ago, Barff (1987) analyzed manufacturing plants in Cincinnati, but did not account for first-order spatial variations in the point pattern.…”
Section: Methodological Issues and Empirical Evidence Of Postsuburbanmentioning
confidence: 99%
“…More than two decades ago, Barff (1987) analyzed manufacturing plants in Cincinnati, but did not account for first-order spatial variations in the point pattern. Accounting for such spatial variations by using a case-control design, Feser and Sweeney (2000) showed that an association between economic linkages and geographic clustering occurs in North Carolina-specifically the clustering of firms in the knowledge-based or technologyintensive sectors.…”
Section: Methodological Issues and Empirical Evidence Of Postsuburbanmentioning
confidence: 99%